2011
DOI: 10.1016/j.anl.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoplasty in children: A review of 91 cases

Abstract: Objectives: There is a marked diversity in the reported success rates for achieving an intact tympanic membrane following tympanoplasty. Controversy exists about the factors thought to influence surgical outcome. These facts have important implications for the selection of patients who would benefit the most. This study reviews the factors thought to determine the anatomical and functional success of tympanoplasty in children. Materials and methods: Retrospective study of the anatomical and functional results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
8
35
0
2
Order By: Relevance
“…We did not find any statistically significant difference between patients who had or had not undergone previous adenoidectomy, a result that agrees with those published by most authors [5,9,15]. Ribeiro et al [7] reported that a previous adenoidectomy in patients older than 10 years seem to be an independent predictor of functional success.…”
Section: Role Of Adenoidecomysupporting
confidence: 92%
See 2 more Smart Citations
“…We did not find any statistically significant difference between patients who had or had not undergone previous adenoidectomy, a result that agrees with those published by most authors [5,9,15]. Ribeiro et al [7] reported that a previous adenoidectomy in patients older than 10 years seem to be an independent predictor of functional success.…”
Section: Role Of Adenoidecomysupporting
confidence: 92%
“…Pignataro et al [9] and Denoyelle et al [16] had reported no significant correlation between age and surgical outcome. Ribeiro et al [7] reported that, a tympanic membrane perforation can be closed at any age and there was no age limit below which perforation should not be closed. Kumar et al [20] in a retrospected study published 2010 reported the results of 132 tympanoplasties performed in children ranging from 6-15 years, no statistical significant difference between age and successful result were found.…”
Section: Patient Agementioning
confidence: 99%
See 1 more Smart Citation
“…High success rates have been reported for pediatric tympanoplasty surgeries performed using fascia grafts. Riberio et al (16) found the success rate as 85.7% in their series including 91 pediatric patients, and Uyar et al (11) reported an anatomical success rate of 90.2% in their series with 41 children. Recently, especially for cases with a lower likelihood of success, such as allergy, tubal dysfunction, reperforation, and total perforation, cartilage has been preferred as the graft material.…”
Section: Discussionmentioning
confidence: 90%
“…The mean age was 13.2±2.7 (8)(9)(10)(11)(12)(13)(14)(15)(16), and the mean follow-up time was 17 (7-36) months. For 25 patients (56.8%), conchal cartilage was used as graft material, and for 19 patients (43.2%), tragal cartilage was used.…”
Section: Resultsmentioning
confidence: 99%